Orofacial Muscle Strength and Associated Potential Factors in Healthy Korean Community-Dwelling Older Adults: A Pilot Cross-Sectional Study - Da-Som Lee; Ji-Youn Kim; Jun-Seon Choi (Applied Sciences)
Most previous studies on orofacial muscle strength have focused on older adults with conditions associated with sensorimotor deficits, such as stroke. However, the modifiable oral health factors that directly impact orofacial muscle strength and swallowing ability in healthy older adults remain unexplored. This pilot study explored the potential factors associated with orofacial muscle strength, particularly oral health conditions, in 70 healthy adults aged ≥65 years living independently without any diseases that cause dysphagia or sensorimotor deficits. The Iowa Oral Performance Instrument (IOPI) was used to assess orofacial muscle strength (tongue elevation, and cheek and lip compression). Statistical analyses were conducted using an independent t-test, one-way ANOVA, and multivariate linear regression. In the final regression models after adjustment, older age and fewer remaining teeth were significantly associated with reduced tongue and cheek strengths (p < 0.05). Socio-demographic factors, such as age, and oral health conditions, such as discomfort in pronunciation or mastication due to oral problems, poor self-rated oral health, and reduced salivary flow, were associated with tongue, cheek, and lip muscle strengths (p < 0.05). Early active oral health interventions can help prevent a decline in orofacial muscle strength in healthy older adults.